Attitudes to personality disorder of staff working in high and medium secure hospitals - Beryl, Rachel; Völlm, Birgit (Wiley, 2017)
The discourse surrounding personality disorder is largely negative, and the diagnosis is considered to be associated with a degree of stigma. This study aimed to investigate current staff attitudes to personality disorder in a high and a medium secure forensic-psychiatric hospital in the UK. Staff attitudes were assessed using the Attitude to Personality Disorder Questionnaire (Bowers & Allan, 2006). The questionnaire was completed electronically by 132 staff. Attitudes to personality disorder in the current study were significantly less positive than in comparable studies in similar settings. Having completed staff training surrounding personality disorder, and being from a non-nursing professional background, were the best predictors of positive attitudes to personality disorder. The findings of this study offer support to the pursuit of improving access to training in personality disorder in forensic settings.